Review of coal fired power plants in Bangladesh - Ahammed, Shakil; Rana, MR; Rony, MA; Hosain, MM; Mamun, MA; Alauddin, Md; Mahmood, MM; Haque, Nurullah; Mahabub, Z; Rahman, MM; Islam, MS; Uddin, Md Nasir; et al. (The Mattingley Publishing Co., Inc, 2020)
This article is based on the current and future coal power plants of Bangladesh. Although, it is known to all that, coal fired power plants are the great sources of carbon and other pollutant ingredients. But it has several positive impacts for developing countries like Bangladesh, where there is a lack of natural resources, lands and unstable economy. Bangladesh government has a vision to supply the electricity all over the country of Bangladesh, from Teknaf to Tetulia, and also for the remote islands also. In this paper, energy demand and vision of Bangladesh government is discussed in section 1. Section 2, gives the answer, why coal fired power plant is necessary for Bangladesh. In section 3, impacts of coal fired power plant is discussed and showed all current power plants in a table. Section 4 comprises with the future of coal fired power plant in Bangladesh.